1978
DOI: 10.1029/gl005i006p00477
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the stress‐concentration mechanism for intraplate earthquakes

Abstract: The hypothesis is examined that concentrations of regional stress in or near mafic intrusions in the felsic continental plate may cause nearby seismicity. If the intrusions are stiffer than the plate, stress concentrations of only 20 or 30 percent above regional values are likely, but intrusions which have been weakened (as by serpentinization) may concentrate stresses more than 200 percent above the regional values. Pockets of seismicity may then occur in the continental plate near the intrusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
85
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 5 publications
12
85
0
2
Order By: Relevance
“…[2] Stress accumulation models of inland faults have been proposed by several studies [e.g., Sykes, 1978;Campbell, 1978]. Iio and Kobayashi [2002] classified these models into two contrastive groups.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Stress accumulation models of inland faults have been proposed by several studies [e.g., Sykes, 1978;Campbell, 1978]. Iio and Kobayashi [2002] classified these models into two contrastive groups.…”
Section: Introductionmentioning
confidence: 99%
“…The results of (Assinovskaya and Soloviev, 1994;Backmanov and Rasskazov, 2000;Guelfand et al, 1976;Gvshiani et al, 1987;Mackey et al, 1977;Sherman and San`kov, 2010;Stein and Yeats, 1989;Zhidkov, 1985;Zhidkov et al, 1975) contributed to develop the methodology of the active structures. In order to obtain the comprehension of the earthquakes localization on intraplate zones were used (Campbell, 1978;Jonston, 1989;Johnston and Kanter, 1990;Leonov, 1995;LeRoy and Mauffret, 1996;Liu and Zoback, 1977;Sbar and Sykes, 1973;Stein, 1999;Sykes, 1978;Zoback, 1992). Our main published results about this field are in the table 4.…”
Section: The Geodynamic Modelmentioning
confidence: 99%
“…Schulte and Mooney 75 presented the updated SCR earthquake catalogue and assessed the correlation of IPEs with ancient rifts on a global scale and found that it has been overestimated in the past (36% occurred in non-rifted crust). Other models have suggested that seismicity in continental interiors could be due to intersecting faults 91 , crustal anomalies 92,93 , etc. Mooney et al 94 used S-wave seismic velocity anomaly 10 to find a correlation with SCR seismicity.…”
Section: Intra-plate Earthquakesmentioning
confidence: 99%